Theoretical fundamentals on the teaching learning process of the technical elements of football (Review) (Revista científica Olimpia, 2020)
The current football for its competitiveness demands coaches, scholars, technical directors, a level of knowledge about the training processes in football, new ways of facing, perfecting the preparation in each sport. The characteristics, dynamic with which this sports discipline is practiced, the complexity of its actions in situations of confrontation in opposition conditions, the need arises to train intelligent, analytical, creative, independent soccer players, with a high technical level of solution in game situations.
Keywords: soccer; dynamic; technical level; opposition conditions